“Discontinuity” as a Concept that affects today’s Art Practice - Yavuz, Nuri; Ayhan Helvacı (European Journal of Social Science Education and Research, 2015)
It has been experienced an alteration which has affected the art environment as in every single area of our lives through the last quarter of the 20th century. When reviewing the artistic works of that time, we encounter “discontinuity” as a fundamental concept in which the philosophers such as Foucault and Baudrillard have constructed its philosophical basis. Discontinuity is defined as the opposite of the “continuity” notion. It corresponds to an environment at which the understanding of continuity predominated on a certain period of time is interrupted and disrupted. This way of thinking also has identified the way of action of artist. Many of contemporary artworks that have a command of a structure devoid of continuity are individually indicators of the altering environment. It is aimed in this study to form an analytical medium on how the discontinuity concept establishes the ground for creating contemporary artworks. As a method, it will be initially determined the extent of the discontinuity concept and then examined within the scope of this concept how selected contemporary artworks have been formed.
Keywords: Contemporary Art, Discontinuity, Alteration